Perau Bangkong as an Iban Weapon of War: A Cultural Materials Analysis (Melayu: Jurnal Antarabangsa Dunia Melayu, 2023)
The Iban community in Sarawak is an agrarian community and does not practice maritime culture in their lifestyle. However, the influence of ngayau practices that have been carried out for generations has enabled them to dominate the ocean using perau bangkong in carrying out war expeditions. The perau bangkong is a symbol of courage and cultural identity in the Iban community. The wars that took place among the Iban ethnic group, or with other ethnic groups such as the Malay, Bidayuh, Urang Ulu and the Brooke army up to the settlement of the Dayak and Banjar communities in Kalimantan have made the perau bangkong famous and feared on the island of Borneo at that time. The objective of this study is to provide an understanding and knowledge about the culture of perau bangkong. This research is in the form of ethnography that uses qualitative methods in its data collection. The findings of the study indicate that perau bangkong has a significant history in the historical legacy of the Iban community in Sarawak. Even though the Iban community no longer practice the ngayau custom, the story and inspiration in the struggle of perau bangkong has spirit in the formation of the community’s identity in the culture and art of their ancestors. The significance of this research is that it can archive and form an understanding through perau bangkong cultural objects as well as celebrate diversity in the cultural togetherness of Malaysians.Full text: PDF